Case Report: Differential diagnosis for tuberous sclerosis and neurofibromatosis type 1 diagnostic pitfall of aggressively enlarged right upper limb - Wei, Cheng-Jiang; Peng, Li-Ling; Chuang, Man-Hon; Wang, Zhi-Chao; Wang, Bin (Frontiers in Oncology, 2022)
Tuberous sclerosis complex (TSC) is an inherited disorder that typically presents with seizures, developmental delay, cutaneous lesions, and facial angiomas. Clinical diagnosis of TSC based on symptoms is sometimes challenging due to its clinical similarities with neurofibromatosis type 1 (NF1), another type of neurogenetic tumor syndrome. Differential diagnosis should be carefully performed based on clinical presentations, imaging, laboratory and genetic testing. Here we presented a case of a patient with an aggressively enlarged right upper limb in the NF1 clinic who was initially suspected of giant plexiform neurofibroma. However, differential diagnosis revealed TSC as the final diagnosis. The treatments for NF1 and TSC vary significantly, and misdiagnoses can lead to serious threat to patients’ health. We also systematically reviewed all previous cases regarding differential diagnoses between NF1 and TSC. This case report can help clinicians make more accurate diagnoses and benefit the potential patient community.